Alternative care takers for children of health care workers during COVID-19 pandemic in Kashmir valley: a cross sectional study - Ahmad, Rabia; Farooq, Uroosa; Ali, Darakshan; Shah, Ab Qayoom (International Journal Of Community Medicine And Public Health, 2023)
Background: COVID-19 pandemic forced health care workers to seek alternatives of child care due to strong standard operating procedures (SOPs). Informal child care workers include patrilineal, matrilineal, immediate family members, neighbours, friends and housemaids. The present study tried to explore and highlight the role of Informal child care workers in alternative spaces. Methods: The present study aimed to reveal new facts about COVD-19 pandemic, its implications in relation to the alternative child care spaces available to the children of health workers in the valley of Kashmir. Total sample size constituted 100 respondents including doctors, Para medicals and other supportive staff chosen through snowball sampling technique. For data collection, a structured questionnaire was constructed and sent to respondents through different social media platforms like Facebook, e-mail ids and WhatsApp. Results: In the study majority of dual career families especially health workers working as frontline COVID warriors in the valley of Kashmir reported that their children were taken care either by alternative care takers mostly patrilocal or matrilocal family members. Conclusions: The study reveals that dual career families of Kashmir prefer largely female members as alternative care takers as compared to male members. The immediate family members are the most preferable choice of Alternative care followed by housemaids.